INTERVENSI DINI BAHASA DAN BICARA ANAK SPEECH DELAY: Early Intervention of Language and Speech In Children With Speech Delay - Tunliu, Fransiska; Amseke, Fredericksen Victoranto (Yayasan Al-Amin Qalbu, 2024)
Language development is one indicator of the overall development of the achievement of cognitive abilities of children Language and speech delays must be recognized by parents from an early age, so that the management provided can maximize the language and speech capacity of children. This research was conducted to describe strategies for implementing early language and speech interventions. talk to children with speech delay The research method used is a qualitative approach with a case study design. This research was conducted at the Happy Living Tesbatan Amarasi PAUD with a total of five children aged 4 years. Data collection techniques through observation, interviews and documents (diaries, checklist documents instrument for assessing achievement of language and speech development, video of early intervention program activities) Method of data analysis using descriptive analysis with a qualitative approach Based on the results of the discussion it can be concluded that there is an increase in language and speech of children with speech delay after being given early intervention Improved language and speech skills can be proven from the results checklist instrument by marking the achievement of language and speech indicators, namely children are able to answer simple questions, express feelings with adjectives, express wishes and mention familiar words